Analisis Yuridis Putusan Mahkamah Konstitusi Terhadap Pengujian Undang-Undang (Studi Putusan MK No. 29/PUU-XXI/2023, No. 55/PUU-XXI/2023, No. 90/PUU-XXI/2023): Juridiсal Analysis of the Constitutional Court's Decision on the Examination of Laws - Khairunnisa Dini Avianti; Yogo Pamungkas (Reformasi Hukum Trisakti, 2024)
This study evaluates the inconsistencies in the decisions of the Constitutional Court (MK) regarding the judicial review of laws, specifically concerning the decision MK No. 29-51-55-90/PUU-XXI/2023. The aim of this study is to understand the reasons behind the differing positions of the MK when reviewing the same article, namely Article 169 letter q of Law No. 7 of 2017 on General Elections. The method used is normative legal research with a descriptive nature, utilizing secondary data as the source. Data collection is conducted through literature study, data analysis is qualitative, and conclusions are drawn using the deductive method. The research findings reveal inconsistencies in the MK's decisions. In Decision No. 90/PUU-XXI/2023, the MK added a new norm by establishing alternative requirements for Article 169 letter q of Law No. 7 of 2017. In contrast, in Decision No. 29-51-55/PUU-XXI/2023, the request to review the same article was rejected on the grounds that the regulation of the minimum age is an open legal policy of the lawmakers and does not violate the 1945 Constitution. This inconsistency raises questions about the integrity of the MK and reduces public trust in the institution. The study recommends that the MK maintain consistency in judicial review decisions to preserve its authority and public trust.